A PP film composition and its preparation method and application

By using a specially made PP film composition in the adhesive of the automotive protective plate, the problems of poor aging resistance and insufficient bonding properties of the existing adhesive are solved, and the high adhesion and aging resistance are improved, thereby reducing the defects of extruded holes.

CN118703122BActive Publication Date: 2025-03-14GUANGDONG KINGFA COMPOSITE MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410637742.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-03-14
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The adhesives of existing automotive protective plates have poor aging resistance and are easy to brittle, and the bonding properties of thermoplastic composite materials and metal plates are poor, which is prone to extrusion hole defects, affecting the bonding effect.

Method used

Using a PP film composition, including copolymer polypropylene, melt stabilizer and binder, the extrusion stability and bonding properties of the film are improved by a specific melt index and grafting rate design.

Benefits of technology

The high adhesion and aging resistance of PP film are achieved, the defects of extrusion holes are reduced, the uniform film output and gram weight are maintained, and the bonding effect of the automobile protective plate is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present invention relates to a PP film composition and a preparation method and application thereof, wherein the components include polypropylene, a melt stabilizer and a binder. The PP film composition of the present invention has good adhesion and aging resistance, and the film is not prone to holes, and can maintain a uniform film output, so that the gram weight of the film is relatively uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adhesive films, and in particular relates to a PP adhesive film composition and a preparation method and application thereof. Background Art

[0002] Against the backdrop of increasingly severe global natural resources and oil resources, new energy vehicles, led by electric vehicles, have begun to emerge. Compared with traditional fuel vehicles, electric vehicles use electricity and do not produce carbon monoxide, carbon dioxide and other gases that are harmful to the environment, thus reducing environmental pollution. The protective plate is installed at the bottom of the vehicle body and is the bearing part of the power battery box of the new energy vehicle. It is used to protect the battery box from damage when it is hit or squeezed by the outside world.

[0003] At present, the protective plate of the car is mainly made of metal alloy materials. This kind of protective plate is not only heavy but also easy to corrode. A combination of thermoplastic composite material and metal plate came into being. Since the metal plate and thermoplastic composite material are different materials, the bonding between the two is poor, and an adhesive is needed to combine the two. The existing adhesives are mainly obtained by glue or ordinary PP modified film. The aging resistance of glue is poor, and it is easy to become brittle after aging and lose the bonding effect; while the ordinary PP modified film material not only has poor aging resistance, but also has a high melt index. Most of them are prepared by the cast film method, which is bound to have holes, affecting the bonding effect of steel plate and thermoplastic composite material. Summary of the invention

[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a PP film composition and a preparation method and application thereof.

[0005] The PP film composition of the present invention comprises the following components by weight:

[0006]

[0007] The polypropylene is copolymer polypropylene, and the melt index under 230°C / 2.16kg is 1-17g / 10min. The melt index test standard is GBT 3682.1~2-2018. The selection of this melt index range is conducive to PP particle film blowing and avoids the occurrence of film holes in the film forming process.

[0008] The mass percentage of polypropylene in the copolymer polypropylene is 80% to 95%; the copolymer polypropylene is copolymerized with ethylene.

[0009] The melt stabilizer is a mixture of propylene-based elastomer and metallocene low-density polyethylene; the melt stabilizer improves the extrusion stability of the PP film, is less likely to cause extrusion hole defects, and has a good film-forming effect.

[0010] The binder is polypropylene grafted with maleic anhydride, the maleic anhydride grafting rate is more than 0.85%, the melt index is 110-200g / 10min at 190°C / 2.16kg, and the melt index test standard is GBT 3682.1~2-2018.

[0011] The test method for the grafting rate is (acid-base titration method): using the principle of acid-base neutralization, first accurately weigh a certain amount of PP-g-MAH and place it in a conical flask, add excess alkali standard solution, heat it to completely neutralize the maleic anhydride on the grafted material, then use the acid standard solution to titrate out the excess alkali, calculate the content of maleic anhydride, and thus obtain the grafting rate.

[0012] Preferably, the polypropylene has a melt index of 2-8 g / 10 min at 230° C. / 2.16 kg.

[0013] If the melt index of polypropylene is too small and the viscosity is too high, the extrusion will be easily damaged and the efficiency will be low. If the melt index is too large and the viscosity is too small, the melt strength will be low, the extrusion stability will be poor, and it will be difficult to blow film. Only when the melt index and melt strength are moderate, it is more suitable for film blowing.

[0014] The propylene-based elastomer is composed of repeating units of isotactic polypropylene and randomly distributed ethylene, and its ethylene mass percentage is 10%-20%; the density of the metallocene low-density polyethylene is 0.91-0.93g / cm 3 .

[0015] Furthermore, the density of the metallocene low-density polyethylene is 0.91 to 0.92 g / cm 3 .

[0016] Preferably, the mass ratio of the propylene-based elastomer to the metallocene low-density polyethylene in the melt stabilizer is (1:0.5) to (1:8), wherein the melt index of the metallocene low-density polyethylene at 190°C / 2.16kg is 0.5-5g / 10min. The melt index test standard is GBT 3682.1~2-2018.

[0017] Further preferably, the mass ratio of the propylene-based elastomer to the metallocene low-density polyethylene in the melt stabilizer is (1:1) to (1:5), wherein the melt index of the metallocene low-density polyethylene at 190°C / 2.16kg is 0.5-2g / 10min.

[0018] The melt stabilizer is a mixture of propylene-based elastomer and metallocene poly-low-density polyethylene, and the melt index of metallocene poly-low-density polyethylene is 0.5-5g / 10min (condition 190°C / 2.16kg). Metallocene low-density polyethylene has a narrow molecular weight distribution and high melt strength, which can significantly improve the melt stability of the system, while the propylene-based elastomer is composed of repeating units of isotactic polypropylene and randomly distributed ethylene, which can improve the compatibility of PP substrate and metallocene poly-low-density polyethylene. Therefore, the two can synergistically improve the extrusion stability of PP film, are not prone to extrusion hole defects, and can maintain a uniform film output.

[0019] Preferably, the polypropylene is grafted with maleic anhydride, the grafting rate is 1-2%, and the melt index is 130-180g / 10min at 190°C / 2.16kg. During the composite process of the protective plate, the adhesive is preferentially enriched on the surface of the film to enhance the interfacial adhesion between the composite plate and the metal plate (such as the metal plate and the aluminum plate). If the melt index is too high, the adhesive is more likely to be enriched on the surface of the film, which is beneficial to the bonding, but not conducive to the extrusion of the film. If the melt index is too low, the adhesive is not easy to migrate to the surface of the film. Therefore, an adhesive with a moderate melt index must be selected to balance the extrusion stability of the film and the adhesion of the metal plate.

[0020] The preparation method of the adhesive comprises: weighing 100 parts of polypropylene, 1-4 parts of maleic anhydride and 0.5-1 part of initiator according to weight, mixing, adding into a twin-screw extruder for reaction extrusion granulation, the temperature is 240-270°C, the speed is 260-320r / min; wherein the initiator is diisopropylbenzene peroxide.

[0021] Preferably, the antioxidant is one or more of a phenolic antioxidant (antioxidant 1010), a phosphite antioxidant (antioxidant 168), and a thioether antioxidant.

[0022] Preferably, by weight, the components include:

[0023]

[0024]

[0025] The invention discloses a method for preparing the PP film composition, comprising: weighing each component by weight, mixing, feeding from a main feeding port of an extruder, melting, extruding, granulating, and film blowing to obtain a PP film; wherein the film blowing process comprises the following steps: a barrel temperature of 180-200° C., a connection zone temperature of 185-205° C., a die head temperature of 195-215° C., and a line speed of 9-12 m / min.

[0026] A battery protection plate of the present invention contains the PP adhesive film.

[0027] The protective plate includes, from bottom to top, a first surface layer, a buffer layer, a first adhesive film layer, a metal plate layer, a second adhesive film layer, a honeycomb core layer, and a second surface layer; wherein the materials of the first adhesive film layer and the second adhesive film layer are the PP adhesive film.

[0028] The first surface layer is far away from the battery surface layer and closer to the ground; the second surface layer is close to the battery surface layer.

[0029] The buffer layer comprises a sawtooth structure, cavities are randomly distributed in the buffer layer, and the cavities are filled with granular materials.

[0030] The buffer layer is designed with a serrated structure and randomly distributed cavities in the buffer layer, and the cavities are filled with granular materials, so that when the protective plate is impacted by the outside world, the stress can be deflected, thereby expanding the stress propagation path, achieving better energy absorption effect, and greatly improving the impact resistance of the protective plate.

[0031] The buffer layer containing a sawtooth structure means that a sawtooth structure is provided on the upper surface and / or the lower surface of the buffer layer.

[0032] The size of the particles is 1-70 microns; the particles are rubber particles.

[0033] The buffer layer has a hardness of 50-80A and a thickness of 0.5-2mm.

[0034] The buffer layer material is TPV.

[0035] The first adhesive film layer and the second adhesive film layer are both PP adhesive films.

[0036] The first adhesive film layer and the second adhesive film layer are used to make the steel plate bond better with the buffer layer and the honeycomb core layer respectively.

[0037] The gram weight of the first adhesive film layer or the second adhesive film layer is 60-150gsm. If the gram weight is too low, the bonding effect between the steel plate and the buffer layer and the honeycomb core will be affected. If the gram weight is too high, the weight of the product will be increased, and the bonding effect will not be further improved.

[0038] The thickness of the metal plate is 0.28 mm to 4.0 mm; the material of the metal plate layer is a steel plate or an aluminum alloy plate, and the aluminum alloy plate refers to an aluminum alloy plate containing a metal Mg-Si system.

[0039] The first surface layer and the second surface layer are both made of continuous fiber reinforced thermoplastic resin composite materials.

[0040] The honeycomb layer serves as an anti-buffer layer.

[0041] The bulk density of the honeycomb core layer is 40 kg / m 3 ~150kg / m 3, with a thickness of 5mm-25mm, which improves the overall stiffness and anti-buffering performance of the material.

[0042] The present invention discloses an application of the PP film composition in a metal plate adhesive.

[0043] The matrix resin of the PP film of the present invention is a thermoplastic polypropylene material, which can make the honeycomb core, buffer layer such as TPV material have good compatibility and bonding performance with metal; maleic anhydride modified polypropylene resin is added to the matrix resin, and it can be well bonded to the metal plate on the surface through surface enrichment; the PP film can still maintain high bonding performance after aging; by selecting a polypropylene resin with a suitable melt index, it can be prepared by a film blowing process to obtain a film material without producing holes (if holes appear, the film cannot be formed); the melt stabilizer has a narrow molecular weight distribution and a high melt strength, can control the strength of the film during film blowing, so that it is not easy to have holes, and can maintain a uniform film output, so that the gram weight of the film is relatively uniform.

[0044] Beneficial Effects

[0045] The PP adhesive film composition of the present invention has good adhesion and aging resistance, and the adhesive film is not prone to holes, and can maintain a uniform film output, so that the gram weight of the film is relatively uniform. DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application. 1. Source of raw materials:

[0047] Polypropylene-1: Copolymer polypropylene, brand K8003, manufacturer: Sinopec Maoming Petrochemical, melt index at 230℃ / 2.16kg is 3g / 10min;

[0048] Polypropylene-2: Copolymer polypropylene, brand EP300M, manufacturer: CNOOC Shell, melt index at 230℃ / 2.16kg is 8g / 10min;

[0049] Polypropylene-3: Copolymer polypropylene, brand Moplen EPF30R, manufacturer: BASELL, melt index at 230℃ / 2.16kg is 15g / 10min;

[0050] Polypropylene-4: Copolymer polypropylene, brand EP548-R, manufacturer: CNOOC Shell, melt index at 230℃ / 2.16kg is 28g / 10min;

[0051] Polypropylene-5: Copolymer polypropylene, brand B8101, manufacturer: Sinopec Yanshan Petrochemical, melt index at 230℃ / 2.16kg is 0.36g / 10min;

[0052] Polypropylene-6: homopolymer polypropylene, brand L5E89, manufacturer: PetroChina Guangxi Petrochemical, melt index at 230℃ / 2.16kg is 3g / 10min;

[0053] Propylene-based elastomer-1, brand 6102, manufacturer: ExxonMobil, ethylene mass percentage 16%;

[0054] Propylene-based elastomer-2, brand 2300, manufacturer: Dow, ethylene mass percentage 13%.

[0055] Metallocene low-density polyethylene-1: brand XP5300, manufacturer Daelim Co., Ltd. of South Korea, melt index at 190℃ / 2.16kg is 1.5g / 10min;

[0056] Metallocene low-density polyethylene-2: brand Elire5400, manufacturer Dow Chemical, USA, melt index at 190℃ / 2.16kg is 1g / 10min;

[0057] Metallocene low-density polyethylene-3: brand NX154, manufacturer SK, melt index at 190℃ / 2.16kg is 3.5g / 10min;

[0058] Metallocene polyethylene, brand name mpe r335hl, manufacturer Qishilu Company, melt index at 190℃ / 2.16kg is 4.7g / 10min; melt stabilizer-1: mass ratio of propylene-based elastomer-1 and metallocene low-density polyethylene-1 is 1:3;

[0059] The mass ratio of melt stabilizer-2: propylene-based elastomer-1 and metallocene low-density polyethylene-1 is 1:1;

[0060] The mass ratio of melt stabilizer-3: propylene-based elastomer-1 and metallocene low-density polyethylene-1 is 1:5;

[0061] The mass ratio of melt stabilizer-4: propylene-based elastomer-1 and metallocene low-density polyethylene-2 ​​is 1:3;

[0062] The mass ratio of melt stabilizer-5: propylene-based elastomer-1 and metallocene low-density polyethylene-3 is 1:3;

[0063] The mass ratio of melt stabilizer-6: propylene-based elastomer-2 and metallocene low-density polyethylene-1 is 1:3;

[0064] The mass ratio of melt stabilizer-7: propylene-based elastomer-1 and metallocene polyethylene is 1:3;

[0065] Preparation method of polypropylene grafted maleic anhydride: 100 parts of polypropylene powder, 1-4 parts of maleic anhydride, and 0.5-1 part of initiator (dicumyl peroxide) are added into a twin-screw extruder for reaction extrusion granulation at a temperature of 240-270° C. and a rotation speed of 260-320 r / min; wherein the polypropylene is grade K8003, manufactured by Maoming Petrochemical Company, with a melt index of 3 g / 10 min at 190° C. / 2.16 kg, and maleic anhydride is commercially available;

[0066] Binder-1: Polypropylene grafted with maleic anhydride, grafting rate 1.45%, melt index at 190℃ / 2.16kg is 155g / 10min; Binder-2: Polypropylene grafted with maleic anhydride, grafting rate 1.5%, melt index at 190℃ / 2.16kg is 130g / 10min;

[0067] Binder-3: Polypropylene grafted with maleic anhydride, grafting rate 1.45%, melt index at 190℃ / 2.16kg is 180g / 10min; Binder-4: Polypropylene grafted with maleic anhydride, grafting rate 1%, melt index at 190℃ / 2.16kg is 160g / 10min;

[0068] Binder-5: Polypropylene grafted with maleic anhydride, grafting rate 1.55%, melt index at 190℃ / 2.16kg is 100g / 10min; Binder-6: Polypropylene grafted with maleic anhydride, grafting rate 1.55%, melt index at 190℃ / 2.16kg is 220g / 10min;

[0069] Binder-7: Polypropylene grafted with maleic anhydride, grafting rate 0.5%, melt index 171g / 10min at 190℃ / 2.16kg; 1,4,7 control the grafting rate by controlling the amount of maleic anhydride, 1-3, and 5-6 control the melt index of polypropylene grafted with maleic anhydride by controlling the amount of initiator, extrusion temperature and rotation speed to break the molecular chain.

[0070] Antioxidant: Antioxidant 1010 and antioxidant 168 are compounded in a mass ratio of 1:1. Antioxidant 1010 and antioxidant 168 are commercially available products.

[0071] 2. Preparation methods of embodiments and comparative examples

[0072] The components are weighed according to weight, mixed, and then fed from the main feeding port of the extruder, melted, extruded, granulated, and blown to obtain a PP film.

[0073] Film blowing process: barrel temperature 180 ~ 200 ℃, connection zone temperature 185 ℃ ~ 205 ℃, die head temperature 195 ~ 215 ℃, line speed 9 ~ 12m / min.

[0074] 3. Test standards and methods

[0075] Test standards and methods for bonding strength: GB / T 1457-2005 Sandwich structure roller peeling strength test method, testing the bonding strength between steel plate / honeycomb core under the adhesion of adhesive film, the adhesive film is selected to be 100 grams;

[0076] Test standard and method for bonding strength after aging: Aging condition: set the temperature to 85±3℃ and humidity to 82%-88%RH in a constant temperature and humidity chamber for 1000h, take it out, and place it at room temperature for another 2h to observe the changes of the composite material board; then carry out the sandwich structure roller peeling strength test according to GB / T 1457-2005 sandwich structure roller peeling strength test method;

[0077] Film appearance: Visually observe under natural light with an illumination of not less than 400lx, recommended illumination of 600lx or a light source close to it, avoid direct sunlight, observe at a distance of 400mm, and check whether there are holes on the film surface. Hole size ≤1mm and number ≤3 / m2 are minor holes; 1mm<hole size ≤4mm or 3<number ≤10 / m2 are more holes; hole size>4mm or number>10 / m2 are large-area holes.

[0078] Film weight: 100cm 2 For materials of different sizes, cut the samples and place them on the round weighing pan of the gram weight balance. The reading on the gram weight balance is the gram weight of the sample. Take 5 samples and weigh them, and the maximum value minus the minimum value will be the gram weight deviation.

[0079] Table 1 Example composition ratio (weight parts) and effect

[0080]

[0081]

[0082] Table 2 Example ratio (weight parts) and effect

[0083]

[0084] Table 3 Comparative proportions (parts by weight) and effects

[0085]

[0086]

[0087] The bonding strength of the PP adhesive film of the present invention reaches above 190 N·mm / mm, and the film-forming effect is good, the film is relatively uniform, and the weight deviation is controlled within 9 gsm.

[0088] Comparative Examples 1 to 3 use PP resins with different melt indices. The melt indices of the resins and the types of the resins have a great influence on the film-forming properties of the films. A large melt indices result in excessive fluidity and the appearance of many holes. A small melt indices result in poor ductility of the resins and poor toughness of the homopolymer resins, which cannot form films.

[0089] Comparative Examples 4 to 6 use different adhesives. The melt index of the adhesive has a certain influence on the film-forming property. When the grafting rate of the adhesive is too low, it has no influence on the film-forming effect, but will reduce the bonding effect of the film.

[0090] Comparative Examples 7 to 9 use different melt stabilizers. Only when the propylene-based elastomer and the metallocene low-density polyethylene work together can the melt stability be improved and the film-forming effect be better.

[0091] Example 16

[0092] A power battery protection plate comprises, from bottom to top, a first surface layer, a buffer layer, a first adhesive film layer, a metal plate layer, a second adhesive film layer, a honeycomb core layer, and a second surface layer.

[0093] The buffer layer contains a sawtooth structure, which improves the impact resistance of the material and reduces the deformation. The buffer layer has randomly distributed cavities filled with granular materials, which improve the energy absorption capacity of the material through physical toughening. Optionally, if the buffer layer contains a sawtooth structure, the upper surface of the buffer layer may be provided with a sawtooth structure, the lower surface may be provided with a sawtooth structure, or both the upper and lower surfaces may be provided with a sawtooth structure.

[0094] The first adhesive film layer and the second adhesive film layer are used to make the steel plate bond better with the buffer layer and the honeycomb core layer respectively. The honeycomb core layer improves the overall stiffness and anti-buffering performance of the material, and the compressibility of the honeycomb core layer and the buffer layer expands the adaptability of the parts.

[0095] The first surface layer and the second surface layer are both made of continuous fiber reinforced thermoplastic resin composite materials. The continuous fiber reinforced thermoplastic resin composite material surface layer and the metal plate layer are combined to avoid some performance shortcomings brought about by a single material.

[0096] The hardness of the buffer layer may be 50-80A, and the thickness may be 0.5-2 mm. For example, the thickness of the buffer layer may be 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.5 mm, 1.8 mm or 2 mm.

[0097] The first adhesive film layer and the second adhesive film layer can be any PP adhesive film in the embodiment. The "steel-plastic combination" of materials is realized through the first PP adhesive film layer and the second PP adhesive film layer, which realizes the lightweight of the product and meets the high performance requirements.

[0098] The metal plate layer material is a steel plate or an aluminum alloy plate;

[0099] The thickness of the metal plate may be 0.28 mm to 4.0 mm; for example, the thickness of the metal plate may be 0.28 mm, 0.3 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm or 4 mm.

[0100] The bulk density of the honeycomb core layer is 40 kg / m 3 ~150kg / m 3 The thickness can be 5mm-25mm. For example, the thickness of the honeycomb core layer can be 5mm, 10mm, 15mm, 20mm or 25mm, etc.

Claims

1. A PP film composition, characterized in that: By weight, the components include: The polypropylene is copolymer polypropylene, and the melt index under the condition of 230°C / 2.16kg is 1-17g / 10min; the mass percentage of polypropylene in the copolymer polypropylene is 80% to 95%; the copolymer polypropylene is a copolymer of polypropylene and ethylene; The melt stabilizer is a mixture of a propylene-based elastomer and a metallocene low-density polyethylene; wherein the propylene-based elastomer is composed of repeating units of isotactic polypropylene and randomly distributed ethylene, and the mass percentage of ethylene is 10%-20%; the mass ratio of the propylene-based elastomer to the metallocene low-density polyethylene in the melt stabilizer is (1:0.5) to (1:8); The adhesive is polypropylene grafted with maleic anhydride, with a grafting rate of more than 0.85% and a melting index of 110-200 g / 10 min at 190° C. / 2.16 kg.

2. The composition according to claim 1, characterized in that The melting index of the polypropylene at 230°C / 2.16kg is 2-8g / 10min; the polypropylene is grafted with maleic anhydride, with a grafting rate of 1-2%, and the melting index at 190°C / 2.16kg is 130-180g / 10min.

3. The composition according to claim 1, characterized in that The density of the metallocene low-density polyethylene is 0.91 to 0.93 g / cm 3 .

4. The composition according to claim 1, characterized in that The metallocene low-density polyethylene has a melt index of 0.5-5 g / 10 min at 190° C. / 2.16 kg.

5. The composition according to claim 1, characterized in that The mass ratio of the propylene-based elastomer to the metallocene low-density polyethylene in the melt stabilizer is (1:1) to (1:5), wherein the melt index of the metallocene low-density polyethylene at 190°C / 2.16kg is 0.5-2g / 10min.

6. The PP film composition according to claim 1, characterized in that: By weight, the components include:

7. A method for preparing the PP film composition according to claim 1, comprising: Weigh each component by weight, mix, Then it is fed from the main feeding port of the extruder, melted, extruded, granulated, and blown to obtain PP film.

8. A battery protection plate, characterized in that: The battery protection plate contains the PP adhesive film described in claim 1.

9. The battery protection plate according to claim 8, characterized in that: The protective plate includes, from bottom to top, a first surface layer, a buffer layer, a first film layer, a metal plate layer, a second film layer, a honeycomb core layer, and a second surface layer; wherein the materials of the first film layer and the second film layer are the PP film described in claim 1.

10. Use of the PP film composition according to claim 1 in a metal plate adhesive.

Citation Information

Patent Citations

  • Aging-resistant glue film for packaging solar cell and preparation method for glue film

    CN102876246A

  • Hot-melt adhesive applicable to PP-R plastic-aluminum stable-state tube and method thereof

    CN109852293A